INCREASING VOCABULARY SIZE OF GRADE VIII STUDENTS AT MTS MUHAMMADIYAH AL-HAQ PALU THROUGH SCAFFOLDING METHOD - Akromah, Hilyatin; Lebagi, Desrin; Said, Mawardin M; Mertosono, Sudarkam R (Universitas Muhammadiyah Makassar, 2025)
Scaffolding is a teaching method in which teachers provide structured, temporary support to help students develop independent learning skills gradually. In the context of English as a Foreign Language (EFL), scaffolding is particularly useful in vocabulary acquisition, especially for young learners who are still building basic language skills. This study aims to find out the effectiveness of the scaffolding method in increasing students’ vocabulary size at MTs Muhammadiyah Al-Haq Palu. Students in grade VIII participated in this research. Two classes were identified as the control and experimental classes in this quasi-experimental research design. The researcher used a pretest and a posttest to collect data. Subsequently, SPSS version 23 was used to analyze the collected data. The result shows that the posttest mean score for students in the experimental class (78.22) was higher than the mean score in the control class (59.56). Furthermore, based on the result of the independence sample t-test, the sig (2 tailed) value (0.001) was lower than 0.05. It indicated that the alternative hypothesis was accepted. Therefore, the scaffolding method can increase the vocabulary size of grade VIII students at MTs Muhammadiyah Al-Haq Palu.